Critical swimming speed of two Iberian cyprinids: the Tagus nase Pseudochondrostoma polylepis and the bordallo Squalius carolitertii - Romão, F. (2012)
The main purpose of this study was to gather swimming performance information for two endemic cyprinids of the Iberian Peninsula to contribute to the optimization of fish ways. Critical swimming speed (Ucrit) was determined for the Tagus nase Pseudochondrostoma polylepis (Steindachner, 1864) and for the bordallo Squalius carolitertii (Doadrio, 1988) in a swimming tunnel. From a total of 80 P. polylepis tested, the mean (± SD) Ucrit observed was 0.78 ± 0.15 ms-1 (c. 3.74 ± 0.93 BL s-1); the 68 S. carolitertii tested presented an Ucrit of 0.54 ± 0.1 ms-1 (c. 4.43 ± 0.74 BL s-1). Significant interspecific differences were found between the Ucrit of the tested cyprinids. Intraspecific comparisons between the Ucrit and the variables of size, sex, condition factor and gonado-somatic index were also made. No sex-or gonad maturation-related differences between the Ucrit were identified, but the robust P. polylepis were found to be stronger swimmers. Water velocities in fish ways for P. polylepis and S. carolitertii should aim, on average, for lower than 0.7 and 0.5 ms-1, respectively.